Kewenangan Penjabat Kepala Daerah Dalam Penyusunan Anggaran Pendapatan Dan Belanja Daerah (APBD) - Pasaribu, Astri Maretta (Universitas Sang Bumi Ruwa Jurai, 2025)
This article discusses the authority of an acting regional head in preparing the Regional Revenue and Expenditure Budget (hereinafter referred to as the APBD). The problem in this paper is that there is no detailed regulation regarding the duties and authority of an acting regional head in managing his regional APBD. The aim of this research is to see the role of an acting regional head in preparing the APBD and to see whether the laws and regulations in Indonesia regulate this authority rigidly. This writing uses normative legal research methods. The results of this research found that in the context of the simultaneous regional head elections which will be held in 2024, there are regulations regulated by the Minister of Home Affairs regarding the authority of acting regional heads in preparing the APBD. The suggestion in this article is that the president should issue a Perppu as a basis for Acting Regional Heads to be able to prepare and submit a Regional Budget Draft Regulation for discussion with the Regional People's Legislation Council (hereinafter referred to as the DPRD)